Preparation method and application of high-temperature-resistant graft modified gel suspension stabilizer

Through the preparation of graft modified gel suspension stabilizer, the problem of reduced suspension stability at high temperature is solved, and the high viscosity and settlement stability of cementing cement slurry at high temperature is achieved, ensuring construction safety and oil and gas development efficiency.

CN119431807APending Publication Date: 2025-02-14CNPC BOHAI DRILLING ENG +1

Patent Information

Application Number
CN202310977749.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-08-04
Publication Date
2025-02-14

AI Technical Summary

Technical Problem

Existing polymer suspension stabilizers are prone to molecular chain breakage at high temperatures, resulting in a reduction in suspension stability performance, affecting the settlement stability of cementing cement slurry and oil and gas extraction efficiency.

Method used

The preparation method of graft modified gel suspension stabilizer is adopted to prepare polymer gel materials through monomer radical polymerization, and chemical grafting reaction with inorganic nanoparticles and grafting agents to form high temperature-resistant grafting modification Gel suspension stabilizer.

Benefits of technology

The viscosity and settlement stability of cementing cement slurry are significantly improved at high temperatures, overcome the defects of poor temperature resistance of commonly used polymer suspension stabilizers, and ensure the safety of cementing construction and the efficiency of oil and gas resource development.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119431807A_ABST
    Figure CN119431807A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of oil well cement admixtures in the field of oil field well cementation, in particular to a preparation method and application of a high-temperature-resistant graft modified gel suspension stabilizer. The invention aims to solve the problem that the molecular chain structure of the existing common high polymer material suspension stabilizer is easy to break at high temperature and loses the suspension stability. The preparation method of the high-temperature-resistant grafted modified gel suspension stabilizer comprises the following steps: step 1, dissolving a monomer in deionized water, introducing protective gas, regulating the pH value of the solution by using a pH regulator, dissolving an initiator and a cross-linking agent in deionized water, and uniformly stirring to obtain a solution A; and filtering, crushing, purifying and drying the polymer prepared by the reaction to obtain the polymer gel material. And 2, dissolving the grafted component inorganic nanoparticles in deionized water, adding the gel material, introducing protective gas, adding a grafting agent, and carrying out a chemical grafting reaction to obtain the grafted modified gel suspension stabilizer.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of oil well cement admixtures in the field of oil field cementing, and in particular to a preparation method and application of a high temperature resistant graft modified gel suspension stabilizer. Background Art

[0002] As my country's shallow and medium-shallow oil and gas reservoirs are gradually depleted during continuous development, the development of deep and ultra-deep oil and gas resources will gradually become normalized. Deep and ultra-deep wells with large burial depths and complex formations and pressure conditions have put forward higher requirements for the various properties of cementing cement slurry systems. The cementing cement slurry system is a sedimentation unstable system of multi-phase coarsely dispersed suspensions. The high temperature of deep formations will accelerate the Brownian motion of solid phase particles in the cement slurry, destroy the viscosity inside the cement slurry, increase free liquid, and increase the density difference between the upper and lower parts of the system. In severe cases, it will affect the cementing quality and oil and gas production efficiency, and even cause cementing accidents.

[0003] At present, the commonly used high-temperature resistant cementing slurry suspension stabilizers are mainly divided into three categories. The first category is inorganic materials, which rely on their own small particle size, large specific surface area, and rapid flocculation to increase the viscosity of the slurry. For example, the high-temperature suspension stabilizer for oil well cement made from inorganic materials in "A high-temperature suspension stabilizer for oil well cement and its preparation method" (CN114368927A) can significantly improve the poor stability and high viscosity of cement slurry in high temperature environments. However, when the amount is large, it is easy to cause the flow performance of cement slurry to deteriorate, affecting the safety of slurry preparation, pumping and even cementing construction.

[0004] The second category is natural polymer materials, which use their water-thickening properties and pseudoplasticity to improve the suspension ability of cement slurry. For example, the suspension stabilizer prepared in "High Temperature Resistant Isolation Fluid Suspension Stabilizer" (CN107177350A) has high efficiency, excellent suspension stability of the system, good rheological properties, and resistance to saturated sodium chloride brine. However, the quality of natural polymer products is unstable, and they are easily decomposed by heat, resulting in reduced viscosity and loss of suspension stability. They are also prone to agglomeration when added directly to water, and uneven mixing will affect the suspension stability effect.

[0005] The third category is artificial synthetic polymer materials. The synthetic polymers have stable performance and are easy to control. They can increase the viscosity of the cement slurry system through hydrophilic groups and higher molecular weight to prevent the sedimentation of solid particles. For example, the suspending agent in "A method for preparing a temperature-sensitive thickening suspending agent for cementing slurry" (CN112724413A) has good chemical stability, good pumping capacity at room temperature, and good thickening effect at high temperature. However, when added in large quantities, there is still severe low-temperature thickening, and there is a significant dilution problem when the temperature exceeds 200°C, which limits the use temperature of the cement slurry system.

[0006] Based on the shortcomings of the existing synthetic suspension stabilizer technology, a gel suspension stabilizer with good viscosity-increasing effect at high temperature is prepared, which has important practical significance for ensuring the safety of cementing construction and the development of oil and gas resources. Summary of the invention

[0007] The purpose of the present invention is to provide a preparation method and application of a high-temperature resistant grafted modified gel suspension stabilizer, which can effectively improve the viscosity of cementing working fluid at high temperatures and maintain the sedimentation stability of low-density or high-density cement slurry systems, thereby solving the problem that the molecular chain structure of existing ordinary polymer material suspension stabilizers is easily broken at high temperatures and loses suspension stability performance.

[0008] In order to solve the above technical problems, the technical solution provided by the present invention is:

[0009] In a first aspect, the present invention provides a method for preparing a high temperature resistant graft modified gel suspension stabilizer, comprising the following steps:

[0010] Step 1: dissolve the monomer in deionized water, stir evenly in a three-necked flask, introduce protective gas, adjust the pH value of the solution to 6-7 with a pH adjuster, dissolve the initiator and cross-linking agent in deionized water, stir evenly, and gradually add dropwise into the three-necked flask, the water bath temperature is 50-80°C, the reaction time is 6-10h, and the polymer obtained by the reaction is filtered, crushed, purified, and dried to obtain a polymer gel material;

[0011] Step 2: dissolving the inorganic nanoparticles of the grafting component in deionized water, mechanically stirring for 6-8 hours, and then ultrasonically dispersing for 1 hour, adding the gel material prepared in step 1, passing protective gas, fully mixing for 1-3 hours, and then adding the grafting agent to obtain a mixed solution, heating to 50-70° C., and performing a chemical grafting reaction for 6-10 hours. After purification and drying, the solution is ground into powder using an electric grinder to obtain a grafted modified gel suspension stabilizer;

[0012] The polymer gel material is obtained by free radical polymerization of monomers, wherein the monomers include monomers with cyclic rigid functional groups, monomers with acrylamide functional groups and monomers with sulfonic acid functional groups.

[0013] Furthermore,

[0014] In step 1, the monomer accounts for 20%-40% of the total solution mass, the initiator accounts for 0.1%-0.6% of the total monomer mass, and the cross-linking agent accounts for 0.3%-1% of the total monomer mass;

[0015] The mass ratio of the monomer having a cyclic rigid functional group, the monomer having an acrylamide functional group and the monomer having a sulfonic acid functional group is 10-20:20-25:5-10.

[0016] Furthermore,

[0017] The monomer having a cyclic rigid functional group is a mixture of one or more of N-vinyl pyrrolidone, phenyl vinyl ether, allyl phenyl ether and vinyl cyclopentane in a certain proportion;

[0018] The monomer having an acrylamide functional group is a mixture of one or more of acrylamide, N,N-diethylacrylamide, and N,N-dimethylacrylamide in a certain proportion;

[0019] The monomer having a sulfonic acid functional group is a mixture of one or more of sodium p-styrene sulfonate, 2-acrylamide-2-methylpropane sulfonic acid, and sodium 2-acrylamide-2-methylpropane sulfonate in a certain proportion.

[0020] Furthermore,

[0021] In step 1, the pH adjusting agent is sodium hydroxide or hydrochloric acid;

[0022] The initiator is a mixture of one or more of ammonium persulfate, potassium persulfate, 2,2-azobisisobutylamidine dihydrochloride, and sodium bisulfite in a certain proportion;

[0023] The crosslinking agent is N,N-methylenebisacrylamide, divinylbenzene, diisocyanate or polyethyleneimine.

[0024] Furthermore,

[0025] The protective gas in step 1 is argon or nitrogen;

[0026] The purifying agent in step 1 is a mixture of one or more of anhydrous methanol, anhydrous ethanol and anhydrous acetone mixed in proportion;

[0027] The drying method in step 1 is freeze drying.

[0028] Furthermore,

[0029] In step 2, the mass ratio of the inorganic nanoparticles, the gel material and the grafting agent is 2-5:5-10:0.5-2, and the three account for 5%-10% of the total solution mass.

[0030] Furthermore,

[0031] The inorganic nanoparticles are a mixture of one or more of nano-silicon dioxide, nano-iron oxide, and nano-aluminum oxide in a certain proportion;

[0032] The grafting agent is a mixture of one or more of vinyl triethoxysilane, vinyl trimethoxysilane and vinyl tert-butyl triperoxide silane in a certain proportion.

[0033] Furthermore,

[0034] The protective gas in step 2 is argon or nitrogen;

[0035] The purifying agent in step 2 is a mixture of one or more of anhydrous methanol, anhydrous ethanol and anhydrous acetone mixed in proportion;

[0036] The drying method in step 2 is freeze drying.

[0037] Furthermore,

[0038] The particle size of the graft modified gel suspension stabilizer is 100-200 meshes.

[0039] In a second aspect, the present invention provides an application of a high temperature resistant graft modified gel suspension stabilizer prepared by the preparation method in cementing cement.

[0040] Based on the above technical solutions, the technical effects that can be achieved by the present invention are:

[0041] (1) The high temperature resistant graft modified gel suspension stabilizer for cementing slurry of the present invention has inorganic modification and cyclic rigid functional groups which effectively improve the high temperature resistance of the gel. The viscosity of cementing slurry is good at high temperature, and the sedimentation stability of cement slurry can be controlled at 0.05 g / cm 3 Within, it overcomes the defect of poor temperature resistance of commonly used polymer suspension stabilizers.

[0042] (2) This method adopts aqueous solution free radical polymerization to avoid the introduction of new impurities during the synthesis process. The prepared high-temperature resistant grafted modified gel suspension has high purity and good chemical stability.

[0043] (3) The high temperature resistant graft modified gel suspension stabilizer for cementing slurry of the present invention can be compatible with a variety of admixtures, and the construction is safe without affecting the engineering performance of the cement slurry. BRIEF DESCRIPTION OF THE DRAWINGS

[0044] In order to more clearly illustrate the specific implementation methods of the present invention or the technical solutions in the prior art, the drawings required for use in the specific implementation methods or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are some implementation methods of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0045] Figure 1 is a thickening curve of cement slurry added with the suspension stabilizer prepared in Example 1 at 180°C;

[0046] Figure 2is a thickening curve of cement slurry added with the suspension stabilizer prepared in Example 2 at 180°C;

[0047] Figure 3 is a thickening curve of cement slurry added with the suspension stabilizer prepared in Example 3 at 180°C;

[0048] Figure 4 is a thickening curve of cement slurry added with the suspension stabilizer prepared in Example 4 at 180°C;

[0049] Figure 5 is a thickening curve of cement slurry added with the suspension stabilizer prepared in Example 5 at 180°C;

[0050] Figure 6 This is a thickening curve of the cement slurry added with the suspension stabilizer prepared in Example 6 at 180°C. DETAILED DESCRIPTION

[0051] The specific embodiments of the present invention are described in detail below. It should be understood that the specific embodiments described herein are only used to illustrate and explain the present invention, and are not used to limit the present invention.

[0052] The endpoints and any values ​​of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values ​​should be understood to include values ​​close to these ranges or values. For numerical ranges, the endpoint values ​​of each range, the endpoint values ​​of each range and the individual point values, and the individual point values ​​can be combined with each other to obtain one or more new numerical ranges, which should be regarded as specifically disclosed in this article.

[0053] Therefore, the following detailed description is not intended to limit the scope of the claimed invention, but merely represents selected embodiments of the present invention. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0054] Example 1

[0055] The three monomers of N-vinyl pyrrolidone, acrylamide and sodium p-styrene sulfonate in a mass ratio of 10:20:5 were dissolved in 100 mL of deionized water respectively, and stirred in a three-necked flask to form a mixed uniform solution, the monomer accounting for 20% of the total solution mass, nitrogen was introduced, and the pH value of the solution was adjusted to 6 with a pH adjuster. The initiator potassium persulfate and the cross-linking agent N,N-methylenebisacrylamide were dissolved in 25 mL of deionized water respectively, and the two accounted for 0.1% and 0.3% of the total monomer mass. The mixture was mixed by magnetic stirring, and gradually added dropwise into the three-necked flask through a constant pressure funnel. The gas was stopped after 30 minutes, the water bath temperature was 50°C, the reaction was carried out for 10 hours, the product was filtered out, crushed into particles, placed in anhydrous ethanol to remove unreacted monomers, and then freeze-dried to obtain a polymer gel material.

[0056] Nano-silicon dioxide was dissolved in deionized water, mechanically stirred for 6 hours, and then ultrasonically dispersed for 1 hour, and a polymer gel material was added, fully mixed for 1 hour, nitrogen was introduced, and a grafting agent vinyl triethoxysilane aqueous solution was added to obtain a mixed solution. The introduction of gas was stopped after 30 minutes. The mass ratio of the three was 2:5:0.5, accounting for 5% of the total solution mass. The water bath temperature was 50°C, and the reaction was carried out for 10 hours. After purification with anhydrous ethanol, freeze-dried, and ground into powder using an electric grinder, a grafted modified gel suspension stabilizer was obtained, and its particle size was about 100 mesh.

[0057] Example 2

[0058] Phenyl vinyl ether, acrylamide, and 2-acrylamido-2-methylpropanesulfonic acid in a mass ratio of 15:22:7 are dissolved in 100 mL of deionized water, respectively, and stirred in a three-necked flask to form a mixed uniform solution, the monomer accounts for 25% of the total solution mass, argon is introduced, and the pH value of the solution is adjusted to 6 with a pH adjuster. The initiator ammonium persulfate and the cross-linking agent divinylbenzene are dissolved in 25 mL of deionized water, respectively, and the two account for 0.2% and 0.4% of the total monomer mass. The mixture is mixed by magnetic stirring, and gradually added dropwise into a three-necked flask through a constant pressure funnel. After 30 minutes, the gas is stopped, the water bath temperature is 55° C., the reaction is carried out for 9 hours, the product is filtered out, crushed into particles, placed in anhydrous methanol to remove unreacted monomers, and then freeze-dried to obtain a polymer gel material.

[0059] Nano-iron oxide was placed in deionized water, mechanically stirred for 7 hours, and then ultrasonically dispersed for 1 hour, and a polymer gel material was added, fully mixed for 1 hour, argon gas was introduced, and a grafting agent vinyltrimethoxysilane aqueous solution was added to obtain a mixed solution. The introduction of gas was stopped after 30 minutes. The mass ratio of the three was 3:5:1, accounting for 6% of the total solution mass. The water bath temperature was 60°C, and the reaction was carried out for 9 hours. After purification with anhydrous methanol, freeze-dried, and ground into powder using an electric grinder, a grafted modified gel suspension stabilizer was obtained, and its particle size was about 120 mesh.

[0060] Example 3

[0061] Allyl phenyl ether, N,N-diethylacrylamide, and sodium p-styrene sulfonate in a mass ratio of 15:25:10 are dissolved in 100 mL of deionized water, respectively, and stirred in a three-necked flask to form a uniformly mixed solution, wherein the monomer accounts for 30% of the total solution mass. Nitrogen is introduced, and the pH value of the solution is adjusted to 6.5 with a pH adjuster. The initiator 2,2-azobisisobutylamidine dihydrochloride and polyethyleneimine are dissolved in 25 mL of deionized water, respectively, and the two account for 0.3% and 0.5% of the total monomer mass. The mixture is mixed by magnetic stirring, and gradually added dropwise into a three-necked flask through a constant pressure funnel. After 30 minutes, the gas introduction is stopped, the water bath temperature is 60° C., the reaction is carried out for 8 hours, the product is filtered out, crushed into particles, placed in anhydrous acetone to remove unreacted monomers, and then freeze-dried to obtain a polymer gel material.

[0062] Nano-alumina was dissolved in deionized water, mechanically stirred for 8 hours, and then ultrasonically dispersed for 1 hour, and a polymer gel material was added, and the mixture was fully mixed for 2 hours. Nitrogen was introduced and a grafting agent, vinyl triperoxide tert-butylsilane aqueous solution, was added to obtain a mixed solution. The introduction of gas was stopped after 30 minutes. The mass ratio of the three was 5:10:1, accounting for 7% of the total solution mass. The water bath temperature was 70°C, and the reaction was carried out for 8 hours. The mixture was purified by anhydrous acetone, freeze-dried, and ground into powder using an electric grinder to obtain a grafted modified gel suspension stabilizer with a particle size of about 150 mesh.

[0063] Example 4

[0064] Vinylcyclopentane, N,N-dimethylacrylamide, and 2-acrylamido-2-methylpropanesulfonic acid in a mass ratio of 17:24:8 are dissolved in 100 mL of deionized water, respectively, and stirred in a three-necked flask to form a mixed uniform solution, wherein the monomer accounts for 35% of the total solution mass. Argon is introduced, and the pH value of the solution is adjusted to 6.5 with a pH adjuster. The initiator sodium bisulfite and the cross-linking agent diisocyanate are dissolved in 25 mL of deionized water, respectively, and the two account for 0.4% and 0.6% of the total monomer mass. The mixture is mixed by magnetic stirring, and gradually added dropwise into a three-necked flask through a constant pressure funnel. After 30 minutes, the gas introduction is stopped, the water bath temperature is 65° C., the reaction is carried out for 75 hours, the product is filtered out, crushed into particles, placed in anhydrous ethanol to remove unreacted monomers, and then freeze-dried to obtain a polymer gel material.

[0065] Nano-silicon dioxide was dissolved in deionized water, mechanically stirred for 6 hours, and then ultrasonically dispersed for 1 hour, and a polymer gel material was added, and the mixture was fully mixed for 2 hours. Argon was introduced and a grafting agent vinyltrimethoxysilane aqueous solution was added to obtain a mixed solution. The introduction of gas was stopped after 30 minutes. The mass ratio of the three was 5:8:1.5, accounting for 8% of the total solution mass. The water bath temperature was 50°C, and the reaction was carried out for 8 hours. The mixture was purified by anhydrous ethanol, freeze-dried, and ground into powder using an electric grinder to obtain a grafted modified gel suspension stabilizer with a particle size of about 170 mesh.

[0066] Example 5

[0067] N-vinyl pyrrolidone, N,N-dimethylacrylamide, and 2-acrylamido-2-methylpropanesulfonate sodium in a mass ratio of 16:21:10 are dissolved in 100 mL of deionized water, respectively, and stirred in a three-necked flask to form a mixed uniform solution, the monomer accounting for 35% of the total solution mass. Nitrogen is introduced, and sodium hydroxide is added to adjust the pH value to 7. The initiator sodium bisulfite and the cross-linking agent N,N-methylenebisacrylamide are dissolved in 25 mL of deionized water, respectively, and the two account for 0.5% and 0.8% of the total monomer mass. The mixture is mixed by magnetic stirring, and gradually added dropwise into a three-necked flask through a constant pressure funnel. After 30 minutes, the gas introduction is stopped, the water bath temperature is 70°C, the reaction is carried out for 7 hours, the product is filtered out, broken into particles, placed in anhydrous methanol to remove unreacted monomers, and then freeze-dried to obtain a polymer gel material.

[0068] Nano-iron oxide was dissolved in deionized water, mechanically stirred for 7 hours, and then ultrasonically dispersed for 1 hour, and a polymer gel material was added, and the mixture was fully mixed for 3 hours. Nitrogen was introduced and a grafting agent, vinyl triperoxide tert-butylsilane aqueous solution, was added to obtain a mixed solution. The introduction of gas was stopped after 30 minutes. The mass ratio of the three was 2:8:1, accounting for 9% of the total solution mass. The water bath temperature was 60°C, and the reaction was carried out for 7 hours. The mixture was purified by anhydrous methanol, freeze-dried, and ground into powder using an electric grinder to obtain a grafted modified gel suspension stabilizer with a particle size of about 200 mesh.

[0069] Example 6

[0070] Vinylcyclopentane, acrylamide, and sodium 2-acrylamido-2-methylpropanesulfonate in a mass ratio of 20:25:9 are dissolved in 100 mL of deionized water, respectively, and stirred in a three-necked flask to form a mixed uniform solution, wherein the monomer accounts for 40% of the total solution mass. Argon is introduced, and the pH value of the solution is adjusted to 7 with a pH adjuster. Initiator potassium persulfate and cross-linking agent divinylbenzene are dissolved in 25 mL of deionized water, respectively, and the two account for 0.6% and 1% of the total monomer mass. The mixture is mixed by magnetic stirring, and gradually added dropwise into a three-necked flask through a constant pressure funnel. After 30 minutes, the gas introduction is stopped, the water bath temperature is 80° C., the reaction is carried out for 6 hours, the product is filtered out, crushed into particles, placed in anhydrous acetone to remove unreacted monomers, and then freeze-dried to obtain a polymer gel material.

[0071] Nano-alumina was dissolved in deionized water, mechanically stirred for 8 hours, and then ultrasonically dispersed for 1 hour, and a polymer gel material was added, and the mixture was fully mixed for 3 hours. Argon was introduced and a grafting agent vinyl triethoxysilane aqueous solution was added to obtain a mixed solution. The introduction of gas was stopped after 30 minutes. The mass ratio of the three was 4:9:2, accounting for 10% of the total solution mass. The water bath temperature was 70°C, and the reaction was carried out for 6 hours. The mixture was purified by anhydrous acetone, freeze-dried, and ground into powder using an electric grinder to obtain a grafted modified gel suspension stabilizer with a particle size of about 200 mesh.

[0072] Comparative Example

[0073] This comparative example uses G30S suspension stabilizer purchased from Weihui Chemical Co., Ltd.

[0074] Performance Testing

[0075] According to the national standard GB / T19139-2012, "Test Methods for Oil Well Cement", a cement slurry blank sample, an example sample with grafted modified gel suspension stabilizer powder added, and a comparative example G30S with G30S suspension stabilizer added were prepared, and their conventional properties were tested respectively. The cement slurry formula is composed of: G-grade oil well cement, quartz sand, microsilicon, retarder, dispersant, lightening material / weighting material, cement slurry suspension stabilizer and water. The amount of water is determined according to the density requirement of the cement slurry. The amount of suspension stabilizer added in the blank sample is 0%, and the amount of suspension stabilizer added in the example sample and the comparative example is 1.5% (calculated based on the total weight of G-grade oil well cement). The test results of the conventional properties of cement slurry are shown in Tables 1, 2 and 3.

[0076] Table 1 Cement slurry ρ = 1.6 g / cm 3 General performance test results

[0077] Table 2 Cement slurry ρ = 1.88 g / cm3 General performance test results

[0078] Table 3 Cement slurry ρ = 2.1 g / cm 3 General performance test results

[0079] Sedimentation stability performance test: Using a high temperature and high pressure thickener, the cement slurry was heated to the target temperature of 180°C and 75MPa, and then continued to cure for 30 minutes, then cooled to 90°C and left to stand for 2 hours. The density of the upper, middle and lower parts of the cement slurry and the volume of the free liquid of the cement slurry were measured in turn to jointly evaluate the high temperature and high pressure sedimentation stability of the cement slurry. The difference in density between the upper and lower parts was less than 0.02g / cm 3 , it is qualified, otherwise, it is unqualified. The test results of cement slurry settlement stability performance are shown in Table 4, Table 5 and Table 6.

[0080] Table 4 Cement slurry ρ = 1.6 g / cm 3 Sedimentation stability test results of suspension stabilizer

[0081] Table 5 Cement slurry ρ = 1.88 g / cm 3 Sedimentation stability test results of suspension stabilizer

[0082] Table 6 Cement slurry ρ = 2.10 g / cm 3 Sedimentation stability test results of suspension stabilizer

[0083] It can be seen from the data in Table 4 that, compared with the comparative example, after high-temperature curing at 180°C, the cement slurry to which the grafted modified gel suspension stabilizer prepared in this embodiment is added has a smaller density difference and better high-temperature stability. The same is true for the data in Tables 5 and 6.

[0084] It can be seen from Tables 1, 2, 3, 4, 5 and 6 that the cement slurry with the grafted modified gel suspension stabilizer has good compatibility with commonly used cementing admixtures, such as fluid loss reducer and retarder, and is safe in construction, does not affect the engineering properties of the cement slurry, and can meet the requirements of high temperature stability of cement slurry.

[0085] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.

Claims

1. A method for preparing a high temperature resistant graft modified gel suspension stabilizer, characterized in that: The following steps are involved: Step 1: dissolve the monomer in deionized water, stir evenly in a three-necked flask, introduce protective gas, adjust the pH value of the solution to 6-7 with a pH adjuster, dissolve the initiator and cross-linking agent in deionized water, stir evenly, and gradually add dropwise into the three-necked flask, the water bath temperature is 50-80°C, the reaction time is 6-10h, and the polymer obtained by the reaction is filtered, crushed, purified, and dried to obtain a polymer gel material; Step 2: dissolving the inorganic nanoparticles of the grafting component in deionized water, mechanically stirring for 6-8 hours, and then ultrasonically dispersing for 1 hour, adding the gel material prepared in step 1, passing protective gas, fully mixing for 1-3 hours, and then adding the grafting agent to obtain a mixed solution, heating to 50-70° C., and performing a chemical grafting reaction for 6-10 hours. After purification and drying, the solution is ground into powder using an electric grinder to obtain a grafted modified gel suspension stabilizer; The polymer gel material is obtained by free radical polymerization of monomers, wherein the monomers include monomers with cyclic rigid functional groups, monomers with acrylamide functional groups and monomers with sulfonic acid functional groups.

2. The method for preparing the high temperature resistant graft modified gel suspension stabilizer according to claim 1, characterized in that: In step 1, the monomer accounts for 20%-40% of the total solution mass, the initiator accounts for 0.1%-0.6% of the total monomer mass, and the cross-linking agent accounts for 0.3%-1% of the total monomer mass; The mass ratio of the monomer having a cyclic rigid functional group, the monomer having an acrylamide functional group and the monomer having a sulfonic acid functional group is 10-20:20-25:5-10.

3. The method for preparing the high temperature resistant graft modified gel suspension stabilizer according to claim 1, characterized in that: The monomer having a cyclic rigid functional group is a mixture of one or more of N-vinyl pyrrolidone, phenyl vinyl ether, allyl phenyl ether and vinyl cyclopentane in a certain proportion; The monomer having an acrylamide functional group is a mixture of one or more of acrylamide, N,N-diethylacrylamide, and N,N-dimethylacrylamide in a certain proportion; The monomer having a sulfonic acid functional group is a mixture of one or more of sodium p-styrene sulfonate, 2-acrylamide-2-methylpropane sulfonic acid, and sodium 2-acrylamide-2-methylpropane sulfonate in a certain proportion.

4. The method for preparing the high temperature resistant graft modified gel suspension stabilizer according to claim 1, characterized in that: In step 1, the pH adjusting agent is sodium hydroxide or hydrochloric acid; The initiator is a mixture of one or more of ammonium persulfate, potassium persulfate, 2,2-azobisisobutylamidine dihydrochloride, and sodium bisulfite in a certain proportion; The crosslinking agent is N,N-methylenebisacrylamide, divinylbenzene, diisocyanate or polyethyleneimine.

5. The method for preparing the high temperature resistant graft modified gel suspension stabilizer according to claim 1, characterized in that: The protective gas in step 1 is argon or nitrogen; The purifying agent in step 1 is a mixture of one or more of anhydrous methanol, anhydrous ethanol and anhydrous acetone mixed in proportion; The drying method in step 1 is freeze drying.

6. The method for preparing the high temperature resistant graft modified gel suspension stabilizer according to claim 1, characterized in that: In step 2, the mass ratio of the inorganic nanoparticles, the gel material and the grafting agent is 2-5:5-10:0.5-2, and the three account for 5%-10% of the total solution mass.

7. The method for preparing the high temperature resistant graft modified gel suspension stabilizer according to claim 1, characterized in that: The inorganic nanoparticles are a mixture of one or more of nano-silicon dioxide, nano-iron oxide, and nano-aluminum oxide in a certain proportion; The grafting agent is a mixture of one or more of vinyl triethoxysilane, vinyl trimethoxysilane and vinyl tert-butyl triperoxide silane in a certain proportion.

8. The method for preparing the high temperature resistant graft modified gel suspension stabilizer according to claim 1, characterized in that: The protective gas in step 2 is argon or nitrogen; The purifying agent in step 2 is a mixture of one or more of anhydrous methanol, anhydrous ethanol and anhydrous acetone mixed in proportion; The drying method in step 2 is freeze drying.

9. The method for preparing the high temperature resistant graft modified gel suspension stabilizer according to claim 1, characterized in that: The particle size of the graft modified gel suspension stabilizer is 100-200 meshes.

10. Use of the high temperature resistant graft modified gel suspension stabilizer prepared by the preparation method according to any one of claims 1 to 9 in cementing cement.

Citation Information

Patent Citations

  • High temperature-resistant insulating fluid suspension stabilizer

    CN107177350A

  • Preparation method of temperature-sensitive tackifying suspending agent for well cementation cement paste

    CN112724413A

  • High-temperature suspension stabilizer for oil well cement and preparation method of high-temperature suspension stabilizer

    CN114368927A

Cited By

  • Temperature-resistant adhesion type supramolecular polymer gel leaking stoppage particles as well as preparation method and application thereof

    CN120082338A